And if there was no state?: critical reflections on Bates, Polanyi and Evans on the role of the state in promoting development - Menocal, Alina Rocha (Third World Quarterly, 2004)
The article review three books about the role of the state in promoting development. It includes "Markets and States in Tropical Africa: The Political Basis of Agricultural Policies," by Robert Bates, "Embedded Autonomy: States and Industrial Transformation," by Peter Evans and "The Great Transformation: The Political and Economic Origins of Our Time," by Karl Polanyi.
Keywords: BATES, Robert H., 1942-; EVANS, Peter, 1944-; Embedded Autonomy: States and Industrial Transformation; Great Transformation, The (Book); Markets & States in Tropical Africa: The Political Basis of Agricultural Policies (Book); nonfiction; state development